Towards a Comparative poetics of Buddha, Kabir and Guru Nanak: From A Secular Democratic perspective - Aparna Lanjewar Bose (Revista Científica Arbitrada de la Fundación MenteClara, 2019)
This article shows how democratic secular values existed 2500 years ago with the Buddha and later during the saint tradition in India, around 14th and 15th century, with Kabir and Guru Nanak even before they were legalized and enshrined in the Indian constitution. No other nation or community in the world probably possesses such a complete consequential philosophy of holistic liberation as India does. And that in a multilingual, multicultural multi-religious Indian ethos there can be a potential dearth of interdisciplinary religious studies or comparative religious departments is in itself the greatest paradox of our times. This paper therefore shall explore the revolutionary emancipatory potential in their philosophical beliefs and egalitarian worldviews that made them popular amongst all sections of the society. It’s a known fact that all the three chose lives as commoners and used the popular language and dialect spoken of their times. All three questioned the efficacy of the Karma Kanda (Vedic rituals) and its hegemonic approach. Their ideological orientations elicit a scientific and an open democratic debate on true nature of things. The rationality, equality and liberal ideology preached by them stands in binary opposition to irrationality, inequality and orthodoxy prevalent. The most important rationale and achievement, extracted out of all the three philosophies, is the psychological freedom ushered to those disqualified and despised because of caste, class, gender and opening up newer vistas of investigation and inquiry that could protect the weak against the onslaught of the strong and mighty. The teachings of Buddha, Kabir, and Nanak move beyond community, religion, language, culture and nation to provide a universal panacea and a paradigm of hope.